Economic Entomology in the 21st Century, as Seen from a Bibliometric Analysis of Two of Its Leading Journals, 2000–2018. Part IV: Beneficial Arthropods Used In the Biological Control of Agricultural Insect Pests. Issue 2 (3rd April 2019) - Stankus, Tony
ABSTRACT: An analysis of two leading journals for economic entomologists employing beneficial arthropods against agricultural insect pests --- the Journal of Economic Entomology, and Biological Control --- uncovered a highly concordant distribution of species used and species attacked. Parasitizing wasps were by far the most common beneficials. These were followed in frequency by predatory versions of the following: true bugs, mites, lady beetles, and lacewings. Assemblages of larger ground beetles and spiders provided good crop protection in fewer but still consequential dilemmas. Familiarity with prominent species will help science librarians who are not entomologists by training, but who may serve students and faculty in agriculture, ecology, or environmental studies, by raising their own awareness of this important means of pest control with less reliance on potentially toxic insecticides.